Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Discovery Learning Pada Siswa SD - Ferryka, Putri Zudhah; Suwartini, Sri; Rofisian, Nela; Rahmawati, Isna (Universitas Muhammadiyah Magelang, 2024)
Learning outcomes are one of the final achievements in learning that need to be considered. Good learning outcomes can of course be determined from many things. The aim of this research is to determine the improvement in learning outcomes of class 2 students at SD Negeri 2 Prambanan through the discovery learning model. This research was motivated by the low student learning outcomes, seen from the student learning outcomes that were still below the KKM as many as 62% of students. This is due to the teacher's lack of innovation in implementing learning models so that students find it difficult to understand the learning material. The type of research used is classroom action research using the Kemmis & Mc Taggart model. This research model consists of four stages, namely planning, implementing actions, observing and reflecting. The research subjects were all class 2A students at SD N 2 Prambanan consisting of 21 students with details of 10 male students and 11 female students. Data collection techniques use observation sheets, measuring learning test results, and documentation. The data analysis technique used is descriptive analysis with percentages. The results in this research show an increase in learning outcomes in each cycle. The learning outcomes of students who have completed cycle 1 are 15 students with a percentage of 71%. In cycle 2 there were 20 students who had completed it with a percentage of 95%. These results reveal a significant increase in student learning outcomes in mathematics in fraction material through the application of the discovery learning model.